Differences in the management of patients requiring an emergency resection for colonic cancer in two European populations. Issue 5 (19th October 2022) - Taylor, John C; Iversen, Lene H; Burke, Dermot; Finan, Paul J; Iles, Mark M; Morris, Eva J A; Quirke, Philip; ,
Abstract: Background: Patients with colonic cancer who require emergency colonic cancer surgery often experience poorer outcomes compared with their elective counterparts. In this setting, several treatments approaches are available. In 2009, Danish guidelines recommended treatment with stent for obstruction in left-sided tumours as a bridge to surgery, if expertise is accessible. The aim of this study was to compare the use of elective and emergency resections for colonic cancer and postoperative mortality in two similar demographic populations. Methods: All patients who underwent a major resection for colonic cancer, between 2005 and 2016 in Denmark and Yorkshire (UK) were identified. The proportion undergoing emergency surgery, the proportion receiving a stent procedure before their resection, and 30-day postoperative mortality were compared between the populations. Logistic regression was used to determine changes in the proportion of those undergoing emergency surgery and 30-day postoperative mortality. Results: Out of 45 397 patients treated during the study interval, 41 880 were selected. Emergency surgery decreased in Denmark from 16.6 per cent in 2005–07 to 12.9 per cent in 2014–16, but increased in Yorkshire (13.5 per cent to 16.8 per cent). Danish patients with left-sided tumours were less likely to undergo emergency surgery (risk ratio 0.90, 95 per cent c.i. 0.82 to 0.99) and an increase in stent use coincided with a statistically significant decrease in emergency surgery in these patients. Thirty-day postoperative mortality in all resections (elective and emergency) decreased in both populations, but a larger decrease was observed in Denmark (7.7 per cent to 3.0 per cent in Denmark and 7.1 per cent to 3.3 per cent in Yorkshire). Conclusion: Patients in Denmark experienced a reduction in the use of emergency resection and increase in stenting procedures, following the policy implemented in some departments of converting potential emergency resections into elective resections. Abstract : This study is part of a large educational intervention programme with an ambitious aim of improving outcomes for colorectal patients in the Yorkshire region of UK (the Yorkshire Cancer Research Bowel Cancer Improvement Programme). The focus of this particular paper compares the use of emergency surgery in patients with colonic cancer from the region with their counterparts in Denmark, and how this may influence the amount of emergency surgery taking place. Patients in Denmark, but not Yorkshire, experienced a reduction in the use of emergency resection, which coincided with an increase in stenting procedures.